Scalable Communication Trace Compression - Krishnamoorthy, Sriram; Agarwal, Khushbu (2010 10th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2010)
Characterizing the communication behavior of parallel programs through tracing can help understand an application's characteristics, model its performance, and predict behavior on future systems. However, lossless communication traces can get prohibitively large, causing programmers to resort to variety of other techniques. In this paper, we present a novel approach to lossless communication trace compression. We augment the sequitur compression algorithm to employ it in communication trace compression of parallel programs. We present optimizations to reduce the memory overhead, reduce size of the trace files generated, and enable compression across multiple processes in a parallel program. The evaluation shows improved compression and reduced overhead over other approaches, with up to 3 orders of magnitude improvement for the NAS MG benchmark. We also observe that, unlike existing schemes, the trace files sizes and the memory overhead incurred are less sensitive to, if not independent of, the problem size for the NAS benchmarks.